Improving Human Development Through Food Security And Economic Growth In Indonesia - Aji Priambodo; Syaeful Bakhri (Cirebon International Journal of Economics and Business, 2026)
As a comprehensive measure of welfare, Indonesia's Human Development Index (HDI) serves as a critical metric guiding targeted policies, with improving household food security and fueling inclusive economic growth representing key avenues to drive sustained gains across health, education, income and poverty reduction. This study examines the vital role of improved food security and inclusive economic growth as strategic drivers that can significantly raise Indonesia's human development outcomes across multiple wellbeing dimensions encapsulated in HDI. This study analyzes the impact of food security and economic growth, on HDI in 34 province in Indonesia. Using panel data regression on national and provincial level data from 2019-2022, result show that food security and economic growth have positive and significant impact in HDI in each province in Indonesia. Improvement in food security and higher economic growth rates correlate with better HDI achievement. These findings indicate that efforts to strengthen food security and accelerate inclusive economic expansion can serve as important pathways for advancing quality of life across Indonesia.